Epistemologizing the Islamic Concept of Resurrection in the Hereafter: A Comparative Study Between al-Ghazālī and Fazlur Rahman - Sibawaihi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The study aims at investigating the epistemology of the concept of resurrection in the hereafter in the views of al-Ghazālī and Fazlur Rahman. This study used documents analysed descriptively and epistemologically. It was found that both figures admitted that resurrection in the hereafter occurs not only in the spirit but also in the body. However, al-Ghazālī’s conception was a dualism of body and soul, while Rahman believed that body and soul are inseparable entities. Epistemologically, al-Ghazālī used text, reason, and intuition as sources of knowledge while Rahman used only text and reason. Al-Ghazālī tended to apply the kalām and intuitive (mystical) methods, while Rahman was more concerned with the philosophical and kalām methods. Discussion by al-Ghazālī was undertaken in theological-metaphysical study of eschatology, while Rahman went beyond mere theological-metaphysical study in which he directed his study towards an ethical-anthropocentric discussion. This comparative study is essential for observing and developing Islamic thought and education.